Distorted images? The artistic images of Spanish fishing industry and fishermen (the end of the 19th century and the beginning of the 20th) - Ansola Fernández, Alberto (Sociología del Trabajo, 2017)
Abstract: In the late nineteenth and early twentieth centuries Spanish fishing and fishermen were engaged in a process of technical, economic and social transformation that was partly leading them towards the industrialization of the industry and towards the proletarianization of their workers. However, in the artistic representations of the literature, painting and cinema of fishing and fishermen, these economic and social changes tended to appear rather blurred and overlapped by the images typical of traditional fishing. How and why this was so in the three artistic manifestations is the object of this study?
Keywords: fishing; fishermen; history; literatura; painting; cinema